Isolation and cellulolytic activity of bacteria from beef cattle feces using rice straw as enrichment substrate - EULIS TANTI MARLINA; YULI ASTUTI HIDAYATI; ELLIN HARLIA; YASIN PRADANA MAULANA; GINA CHYNTHIA KAMARUDIN PUTERI (Society for Indonesian Biodiversity, 2026)
Abstract. Marlina ET, Hidayati YA, Harlia E, Maulana YP, Puteri GCK. 2026. Isolation and cellulolytic activity of bacteria from beef cattle feces using rice straw as enrichment substrate. Biodiversitas 27 (6): d270617. https://doi.org/10.13057/biodiv/d270617. Beef cattle (Bos indicus/taurus) feces contain diverse microbial communities with potential roles in lignocellulosic biomass transformation. This study aimed to evaluate the initial decomposition of rice straw and beef cattle feces, using this information as a basis for isolating and preliminarily identifying cellulolytic bacteria from beef cattle waste. Rice straw was mixed with beef cattle feces to initiate decomposition for 7 days. Changes in chemical composition and structure were assessed using fiber fraction analysis and Scanning Electron Microscopy (SEM). The addition of cattle feces reduced Acid Detergent Fiber (ADF) from 51.36% to 42.31%, Neutral Detergent Fiber (NDF) from 72.08% to 60.82%, lignin from 12.89% to 7.40%, cellulose from 38.47% to 34.91%, and hemicellulose from 20.72% to 18.51%. SEM showed increased surface roughness and fiber degradation (loosening and fragmentation), with structural changes that can be attributed to microbial activity. Based on this finding, microbial enrichment was carried out with cattle feces and rice straw, with the addition of molasses as a nutrient source for microbial growth. Seven bacterial isolates were obtained, among which three (LS-6, LS-11 and LS-14) exhibited the highest cellulolytic activity on Carboxy-Methyl Cellulose (CMC) agar and dinitrosalicylic acid (DNS). Molecular level identification of these isolates through 16S rRNA gene sequence revealed that these isolates were closely affiliated with Bacillus safensis and Bacillus pumilus group. The results suggest that the isolates exhibit cellulolytic activity under the test conditions and may contribute to lignocellulose degradation. This study provides a first step for further research on cellulolytic bacteria from beef cattle feces for the effective use of lignocellulosic biomass.